Sacred music, religious desire, and knowledge of God : the music of our human longing - Perlmutter, Julian ([London, England] : Bloomsbury Academic, 2020)
"Many people find sacred choral music profound and deeply evocative, even in societies that seem to be turning away from religious belief. In this book, Julian Perlmutter examines how, in light of its wide appeal, sacred music can have religious significance for people regardless of their religious convictions. By differentiating between doctrinal belief and the desire for God, Perlmutter explores a longing for the spiritual that is compatible with both belief and 'interested non-belief'. He describes how sacred music can elicit this kind of longing, thereby helping the listener to grow in religious openness. The work of Thomas Merton is also analyzed in order to show that musically-elicited desire for God can be incorporated into the Christian practice of contemplative prayer, aimed ultimately at a union of love with God. By exploring connections between desire, knowledge and religious practice, this engaging account illustrates how sacred music can have a transformative effect on one's wider spiritual life. Of particular interest to philosophers and theologians, the book makes a novel contribution to several topics including religious epistemology, the philosophy of emotion and aesthetics."--
1. Introduction -- 2.Sacred music, longing and openness -- 3. Desire and knowledge -- 4. Music and affect -- 5. Sacred music and knowledge by desire: The account applied -- 6. Religious desire and contemplative prayer -- 7. General conclusion.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Music -- Religious aspects; Philosophy of religion; Electronic books